Rocking the Boat? Church NGOs and Democratization in Zimbabwe - Dorman, Sara Rich (Oxford University Press, 2002)
Historically, relations between church and state in independent Zimbabwe have tended to be cooperative and on-confrontational. However, in 1997 the Zimbabwe Council of Churches (ZCC) initiated the National Constitutional Assembly (NCA), leading to the government’s defeat in the first post-independence referendum and setting the stage for the violent elections of June 2000. Nevertheless, as the NCA developed the strength and capacity which enabled it to challenge the status-quo, the ZCC withdrew. As a key-player said ‘… as churches we had to take issues that don’t raise too much dust or rock the boat too much, but the boat was rocking.’ This suggests that although the church may play a critical role in opening up space for debate, the state may still co-opt and weaken churches and other groups, in its effort to retain hegemony. Churches and church-NGOs relate ambiguously to both the state and to society – in both colonial and post-colonial Zimbabwe – and remain vulnerable to political, economic, and social pressures. Theories of democratization – and in particular the role played by churches and NGOs – must begin to recognize the complexity and ambiguity of state-society relations as detailed in this study.
Keywords: Zimbabwe; NGOs; Africa